Madagascar - Three Years into the Crisis : An Assessment of Vulnerability and Social Policies and Prospects for the Future, Volume 2. Background Papers - World Bank (Washington, DC, 2013)
The report is divided into two volumes. The first volume includes the fundamental content of the report. It is organized as follows. Chapter one provides a conceptual framework to analyze risk and vulnerability and provides a definition of social protection. Chapter two assesses the main risks faced by the Malagasy population as well as its vulnerability profile. Chapter three reviews Madagascar's social protection policies, the institutions responsible for social protection and the financial resources allocated to social protection by the government, donors and Non-Governmental Organizations (NGOs). Chapter four proceeds with a description and analysis of the main social protection programs presently under implementation in Madagascar. Chapter five builds on the previous chapters but also on the experience of other low income countries, especially in Africa. It outlines the main principles of a social protection strategy and recommends priority actions for implementation including in the immediate aftermath of a resolution to the current political crisis. As such, this report is intended to contribute to future governments' own formulation and implementation of a social protection strategy. The second volume includes a number of background papers that were commissioned during the preparation of this report. These papers are as follows: strategic directions for social protection in Madagascar by Anthony Hodges; Poverty, Vulnerability and Sources of Risks by Tiaray Razafimanantena; vulnerability analysis by INSTAT; Review of Social Protection Programs by Julia Rachel Ravelosoa; analysis of public spending on social protection in Madagascar by Maminirinarivo Ralaivelo; description and Analysis of the Tsena Mora Program by Maminirinarivo Ralaivelo; review and analysis of spending on social protection by NGOs by Francis Hary Soleman Kone; case study: cash transfer and other forms of education support for children of poor households by Brigitte Lalasoa Randrianasolo and payment mechanisms to transfer cash to the Poor in Madagascar by Josiane Robiarivony Rakotomanga.